The Use of Information and Communication Technologies in Poverty Alleviation in Rural Communities in the Central Region of Ghana - Sam, J (university of Ghana, 2013)
Information and communication technologies (ICTs) have the potential to improve the welfare of the poor by providing opportunities to increase social capital; improve availability of market information; creation of new economic opportunities; improve economic efficiency and competitiveness; better access to health and education facilities and more efficient and effective governance. In spite of the significant ICT development and growing recognition of their benefits, there are concerns about the role of ICTs in facilitating communication of information for sustainable livelihoods and poverty alleviation in Ghana, particularly in rural areas. There is a lack of clear empirical evidence between ICTs, livelihoods and poverty in Ghana as the few studies undertaken have not yielded sufficient evidence to comprehensively understand the subject. These studies were also confined to mobile phones to the exclusion of radio and television which are widely used in rural communities. This is the research gap the study intended to fill. The overall research question was: what is the use of some information and communication technologies (mobile phones, radio and television) in poverty alleviation at the individual and household levels in two rural districts of the Central Region of Ghana. The study was guided by the Sustainable Livelihoods Framework (SLF) as developed by the United Kingdom Department for International Development (DfID). The case study research design, with a combination of both quantitative and qualitative methods of data collection with the quantitative as the dominant method used for the study. Data was collected through the use of questionnaire, focus group discussion and key informant interviews. The respondents for the study was made up of four hundred and twelve heads of household, fifty one focus group participants and eleven key informants. Data collected was analyzed using the Statistical Package for Social Sciences (SPSS) version 21.0. Descriptive statistics including frequencies and percentages were computed and used to summarize data. The research results obtained were presented in a very simple and non-technical form by using percentage and frequency tables, and charts. Inferential statistics was used and various tools for inferring meaning, including measures of central tendency (mostly the mean and standard deviation), and chi-square evaluations were made in order to appreciate the deeper implications of the results and to confirm the results which the percentages will not be able to bring out clearly. The study established that most of the heads of household were below the age of 50 years with Junior Secondary School Certificate as the highest qualification obtained by majority of them. Crop farming was the principal occupation and main source of income with about a third of the respondents earning less than GH¢500 ($250) per annum. The respondents had modest accommodation with electricity and pipe borne water available in some of the houses. It was found that majority of the respondents had access to and made use of mobile phones more than radio and television. The ICT tools under study have been beneficial to the owners as well as non-owners of the tools since they share them with the owners. Network coverage as well as quality of service was generally good. Cost of mobile phone services was generally high and some innovative means have been found to reduce it. Time of broadcast, language and programme content are the determining factors for watching television or listening to radio and most of the respondents watch and listen to entertainment, musicals, local and international news The study established that the ICTs under study have played significant roles to reduce poverty and improve livelihoods through expanding and strengthening social networks, overcoming social and economic exclusion, dealing with emergencies, reducing cost and increasing productivity, minimizing physical risks, improving efficiency of activities, increasing entertainment options, increasing awareness and general knowledge of respondents to participate in development activities. Some detrimental effects and barriers to effective access and use to the studied ICTs are noted. These include: increased immoral behavior, exposure to unethical information, high cost of ICTs and erratic power supply, among others. Recommendations made include: rural development strategies incorporating ICTs, social protection policies and improving infrastructure, among others with the view that when these are implemented it would go a long way to improve access to and use of the studied ICTs. This would eventually improve livelihoods, well-being and reduce poverty. The purpose for which the study was conducted was achieved and areas have been identified for further research.
Thesis (PhD) - University of Ghana, 2013
Keywords: Information and Communication Technologies; Poverty Alleviation; Rural Communities; Ghana; Sustainable Livelihoods Framework; ICT development